(untitled) (Revista Iberoamericana de Bioética, 2021)
This article seeks to analyze the implications of the concept of life as adopted by the American biochemist Van Rensselaer Potter in his bioethical theory. An analytical literature review was conducted to: a) define Potter’s perception of the concept of life; as well as b) analyze the extent to which the characteristics of this phenomenon are expressed in the development of a science of survival. Potter borrows fundamental concepts from biocybernetics to explain the living organism, which allows him to describe bioethics as a cultural feedback mechanism aimed at human survival.